2008
DOI: 10.1183/09031936.00137006
|View full text |Cite
|
Sign up to set email alerts
|

Chronic bronchitis sub-phenotype within COPD: inflammation in sputum and biopsies

Abstract: The presence of chronic bronchitis predicts a more rapid decline of forced expiratory volume in one second (FEV1) in patients with chronic obstructive pulmonary disease (COPD). The hallmark of COPD is airway inflammation. It was hypothesised that COPD patients with chronic bronchitis are characterised by a distinct inflammatory cell profile, as measured in bronchial biopsies and sputum.From 114 COPD patients (male/female ratio 99/15, mean¡SD age 62¡8 yrs, current smoking 63%, post-bronchodilator FEV1 63¡9% pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(35 citation statements)
references
References 45 publications
(58 reference statements)
4
26
1
1
Order By: Relevance
“…Preliminary results from our own institution, from a protocol approved by our Institutional Review Board and with written consent from participants, further suggest that patients with chronic bronchitis symptomatology have increased 18 F-FDG uptake compared with those without such symptoms ( Fig. 2; data published in abstract form from Chen et al (52)), in line with the known increased lung inflammation that occurs with chronic bronchitis (55). Together, the available data suggest that 18 F-FDG uptake may be useful in distinguishing inflammatory phenotypes within COPD.…”
Section: Disease-specific Investigations Copd and Asthmasupporting
confidence: 55%
“…Preliminary results from our own institution, from a protocol approved by our Institutional Review Board and with written consent from participants, further suggest that patients with chronic bronchitis symptomatology have increased 18 F-FDG uptake compared with those without such symptoms ( Fig. 2; data published in abstract form from Chen et al (52)), in line with the known increased lung inflammation that occurs with chronic bronchitis (55). Together, the available data suggest that 18 F-FDG uptake may be useful in distinguishing inflammatory phenotypes within COPD.…”
Section: Disease-specific Investigations Copd and Asthmasupporting
confidence: 55%
“…Although neutrophils are clearly associated with chronic bronchitis, it is likely that many immune cell populations are involved in the pathogenesis of this disease. Interestingly, there are few differences in the cellular content of bronchial biopsies taken from patients with COPD with and without chronic bronchitis (122) although one study has suggested a predominance of eosinophils in airway secretions when chronic bronchitis is present (123), however this observation has not been replicated. The numbers of CD8+ lymphocytes in bronchial tissue relate inversely with FEV 1 (122) and have been shown capable of causing lung tissue damage both by their own cytotoxicity and by recruiting macrophages by secreting IFN-.…”
Section: Immunology and Inflammation In Chronic Bronchitismentioning
confidence: 89%
“…50 Among COPD patients, a group present chronic bronchitis, and COPD groups with or without chronic bronchitis have similar high amounts of macrophages in bronchial biopsies. 51 Therefore, we believe that any COPD group with high TNF-a levels in bronchial macrophages could benefit from an anti-TNF-a intervention to inhibit MUC5B þ GCH. However, our hypothesis needs to be validated using HBEC from patients, as bronchus cells from a healthy donor can be genetically and functionally different to diseased airway epithelial cells.…”
Section: Discussionmentioning
confidence: 99%